2020
DOI: 10.34172/jrhs.2020.06
|View full text |Cite
|
Sign up to set email alerts
|

The Suicide Rate in the Elderly Population of Iran between 2008 and 2014

Abstract: Background: We aimed to investigate the suicide rate led to death in the elderly population of Iran between 2008 and 2014. Study design: A cross-sectional study. Methods: The present study was conducted on all suicide-related deaths in elderly people (≥65 yr) during the years 2008 to 2014 reported to the Iranian Legal Medicine Organization. For data collection, legal medicine standard form was used and the cases were classified by age, gender, suicide way and time (year). The incidence of death from suicide wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Totally, the incidence rate of suicide has increased slightly during the study period from 2007 to 2018. The pattern of suicide trend in the present study is in line with the trend of all Iranian completed suicide cases reported by Razai et al [10].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Totally, the incidence rate of suicide has increased slightly during the study period from 2007 to 2018. The pattern of suicide trend in the present study is in line with the trend of all Iranian completed suicide cases reported by Razai et al [10].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, males have committed suicide more than two times than females. According to the WHO report in 2016, the mortality rate by suicide in males has been about twice that of females [10]. Likewise, the male to female sex ratio was 1.4 in the Zhong study, and suicide in men has been observed 40% higher than in women [21].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations